A soft and stretchable electronics using laser-induced graphene on polyimide/PDMS composite substrate - Hao Wang; Zifen Zhao; Panpan Liu; Xiaogang Guo (npj Flexible Electronics, 2022)
Abstract The one-step fabricated laser-induced graphene (LIG) has the advantages of low cost, patterning of various desired geometries, and high sensitivity. However, the robustness of substrates imposes certain constraints on their applications in stretchable devices. In this paper, the substrate composed of polydimethylsiloxane (PDMS) and polyimide (PI) particles is proposed to serve as the platform to manufacture LIG. Ascribing to the inherent soft and stretchable attributes of the PI/PDMS composite substrate, the LIG-based sensors can fit complex 3D configurations or bear a mechanical tension over 15%. Notably, the fluence of the laser is experimentally and theoretically determined as the only principle to characterize the formation of conductive LIG on PI/PDMS composite greatly facilitating the selection of the allowable laser scanning parameters to form the desired LIG-based devices. Three demonstrations are conducted to highlight the superiority and the potential of this soft and stretchable LIG-based system in wearable electronics and soft robots.